2023
DOI: 10.1111/nin.12584
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' ways of talking about their experiences of (in)justice in healthcare organizations: Locating the use of language as a means of analysis

Abstract: Nurses have their own ways of talking about their experiences of injustice in healthcare organizations. The aim of this article is to describe how nurses talk about their work‐life experiences and discuss the discursive effects that arise from nurses' use of language regarding their political agency. To this end, we present the findings garnered from a study focused on exploring how nurses deploy their political agency to project their idea of social and political justice in public healthcare organizations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…However, this is too limited as organizational interaction is more complex than just organizational hierarchy. In other words, agents have certain role expectations (Anglin et al, 2022) of themselves and others and this is materialized in influence and talk (Lopez‐Deflory et al, 2023b). Kee et al (2021) highlight that an excessive focus on hierarchy can diminish the value of expertise, adversely affecting organizational performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is too limited as organizational interaction is more complex than just organizational hierarchy. In other words, agents have certain role expectations (Anglin et al, 2022) of themselves and others and this is materialized in influence and talk (Lopez‐Deflory et al, 2023b). Kee et al (2021) highlight that an excessive focus on hierarchy can diminish the value of expertise, adversely affecting organizational performance.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we, therefore, zoom in on how members of executive hospital boards (hereafter: board member(s)) and nurses use talk as a relational dance of positions in times of crisis. Although the importance of talk has been acknowledged for frontline nursing work (Barcelona et al, 2023;Dahlke & Hunter, 2020;Lopez-Deflory et al, 2023b;Marey-Sarwan et al, 2022) it seems overlooked in the nursing leadership and governance literature (see Cummings et al, 2021;Kanninen et al, 2021). However, Verhoeven et al (2023) showed that such a discursive leadership perspective can be supportive for comprehending the relational processes and interdependencies between board members and nurses.…”
Section: Introductionmentioning
confidence: 99%